Mechanization network for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The Euro-African Association of Agricultural Mechanization Centres is now working on ways to improve information exchange between its different members. Two projects are currently under way: the publication of a directory of manufacturers of...